Discordance between patients’ perception and endoscopic assessment of disease activity in ulcerative colitis - Boilève Juliette; Trang-Poisson Caroline; Flamant Mathurin; Bouguen Guillaume; Goronflot Thomas; Freyssinet Marie; Kerdreux Elise; Bourreille Arnaud; Le Berre Catherine (Therapeutic Advances in Gastroenterology)
Background: Discrepancies between symptoms and endoscopy exist in patients with ulcerative colitis (UC). Most studies focused on patient-reported outcomes-2 rather than their overall perception of disease activity. Objectives: The objectives were to assess the concordance between the patient global assessment (PtGA) and the endoscopic evaluation, to analyse the factors associated with agreement and to describe the concordance between the patient’s and the physician’s perception of UC activity. Design: Prospective, observational study. Methods: Patients with UC were consecutively included at the time of flexible sigmoidoscopy. The concordance between the Mayo endoscopic subscore (MES) and the PtGA was evaluated. The factors related to concordance were investigated, including the inflammatory bowel disease (IBD)-Disk items that were completed by all patients. Results: Out of 104 analysable patients, 32.7% demonstrated complete alignment with the MES. The more the disease was objectively active, the more the patients were concordant, as reflected by the statistically significant differences between concordant and discordant patients in the median (interquartile range) MES (2 (1–2) vs 1 (0–2), respectively ( p  = 0.002)), Ulcerative Colitis Endoscopic Index of Severity (3 (2–5) vs 1 (0–3), respectively ( p  = 0.001)) and physician global assessment (whether on a qualitative scale as part of the Mayo score ( p  = 0.003) or on a 10 cm-visual analogue scale: (4 (1–6) vs 1 (0–3), respectively ( p  < 0.001)). Over two-thirds of discordant patients perceived their disease as more severe than the endoscopy suggested. While stool frequency did not differ between concordant and discordant patients ( p  = 0.093), rectal bleeding ( p  = 0.002) – predictably – and more interestingly, abdominal pain ( p  = 0.006) and bowel urgency ( p  = 0.006), emerged as symptoms strongly associated with improved concordance between patient perception and endoscopic evaluation. Conclusion: Discrepancies between patient-reported disease activity and endoscopy are prevalent in UC. In addition to rectal bleeding, abdominal pain and bowel urgency may be more accurate to reflect clinical disease activity than stool frequency.